ADDIE-Based vocational e-commerce training for students with mild intellectual disabilities: Charcoal briquette study - Nurlatifah, Safira; Septiana, Fajar Indra (STAI Auliaurrasyidin Tembilahan, 2025)
This study developed and evaluated a vocational program integrating charcoal briquette production and e-commerce marketing for students with mild intellectual disabilities. Employing the ADDIE instructional design model (Analysis, Design, Development, Implementation, Evaluation) within a descriptive qualitative framework, this pilot case study focused on a single 11th-grade student at SMALB. The participant was selected based on identified challenges in comprehending fundamental marketing concepts. Data were collected through interviews, observations, documentation, and focus group discussions, and analyzed using thematic analysis. Findings revealed that while the student successfully engaged in the hands-on production tasks, significant scaffolding was required for digital marketing activities on the Shopee platform. The development of a contextualized learning module enhanced the student's understanding of basic entrepreneurial concepts; however, the inherent complexity of the e-commerce interface presented a substantial learning barrier. The study concludes that integrating digital marketing into vocational education holds promise for students with intellectual disabilities but must be deliberately adapted to their cognitive abilities. Success is contingent upon scaffolded digital literacy training, the use of simplified and interactive learning media, and sustained teacher support to ensure the program's long-term viability and potential for scaling.